Design and Preparation of PU/EP Blend Resin Grafted by Hydrophilic Molecular Segments - Gang Lu (MDPI AG, 2021)
Film-forming resins, as carriers of antifouling coatings, play an essential role in the functional performance of coatings. With the gradual promotion of coatings in the field of marine antifouling, the preparation of film-forming resins containing hydrophilic chain segments is urgently needed to give full play to the functional and time-sensitive performance of antifouling coatings. In this paper, the single-ended isocyanate group (NCO) polyurethane (PU) prepolymer with hydrophilic chain segments was prepared and grafted onto an epoxy resin (EP) molecular chain to obtain the PU/EP grafted blend. Successful preparation of the PU/EP grafted blends was confirmed by infrared spectrum analysis. Simultaneously, the grafted blend was cured, and its hydrophilicity and mechanical properties were also tested. The results demonstrate that the grafted method can effectively improve the hydrophilicity of the film-forming resin while maintaining its mechanical properties. It can be concluded from the hydrophilic and mechanical properties of the materials that the comprehensive properties of PU/EP grafted blends are the best when the PU content is between 40% and 50%. The hanging plate test showed that the antifouling effect of the antifouling coating prepared by hydrophilic modified PU/EP film-forming resin was better than that of the traditional antifouling coating under the experimental conditions.